Building New Andhra Progress of the First Plan - Planning Commission (Planning Commission, 1956)
India became politically free in 1947 but her economy was still obsolete. She inherited all the economic malaise to which a subject country is destined. The unprogressive Indian economy was characterized by unutilized or underutilized man power on the one hand and unexploited natural resources on the other. In fact the problem in India was poverty amidst potential plenty. And the Second World War had subjected it to further severe strain.
Planning and Development Department, Andhra State